Are fiscal decentralization and institutional quality poverty abating? Empirical evidence from developing countries - Kumba Digdowiseiso (Cogent Economics & Finance, 2022)
Fiscal federalism theorists have long been intrigued by the relationship between fiscal decentralization and poverty. Few people, however, consider cross-country research of similar linkages in developing countries. This research will provide new empirical evidence on the relationship between fiscal decentralization and poverty. It focuses on how the function of institutional quality can explain the relationship between fiscal decentralization and poverty in 53 developing countries from 1990 to 2014. The findings showed that a process-based approach as well as an outcome-based institutional-quality approach could explain the relationship between fiscal decentralization and poverty. In the case of democracy, revenue decentralization was found to be negatively and significantly related to poverty. In the case of, both revenue and expenditure decentralization were negatively and significantly associated with poverty.
Keywords: 330; Fiscal decentralization; institutional quality; poverty; subnational government analysis; developing countries